Pengaruh Digital Marketing Terhadap Brand Awareness Podcast Berbahasa Jawa (Universitas Negeri Surabaya, 2022)
Until now, technology has grown rapidly and has produced business tools for business people to increase brand awareness of a product to consumers. One of them is the Mendoan Podcast, which uses a digital marketing strategy to increase brand awareness among consumers or their listeners. The main purpose of this research is to find out whether there is an influence between